A comprehensive evaluation of piezoresistive response and percolation behavior of multiscale polymer-based nanocomposites. (March 2020) - Haghgoo, M.; Hassanzadeh-Aghdam, M.K.; Ansari, R.
Abstract: This article investigates electrical conductivity and piezoresistivity of carbon nanotube (CNT)-polymer nanocomposites using an efficient analytical model. The effects of chopped carbon fibers on the electrical conductivity and percolation behavior of multiscale polymer-based nanocomposites containing CNTs are examined at various maximum angular orientations and different polymer matrix barrier heights. The multiscale nanocomposite (MSNC) electrical conductivity and percolation onset are found to be dependent on the carbon fiber and CNT geometry and dispersion. The tunneling effect is discussed as an important mechanism to explain the low percolation threshold and nonlinear electric behavior of MSNC. A comparison between nanocomposites filled with CNTs and MSNC reinforced with CNTs and chopped carbon fibers demonstrates different percolation behaviors. Moreover, the influences of CNT position and orientation changes on the piezoresistivity of polymer nanocomposites are studied. Resistance change ratio as a function of applied strain demonstrates a non-linear behavior due to tunneling resistance change between CNTs.